Analysis of the Q.A.D. algorithm for an homogeneous multiprocessor computing model with independent memories - Spyropoulos, C.D.; Evans, D.J (International journal of computer mathematics, 1985)
This paper presents the extreme performance of the promising Q.A.D. algorithm, for scheduling independent jobs under few pre-set ordering rules on the examined model, when the mean-flow time is the performance criterion. Further, an algorithm, based on the idea of Q.A.D., with complexity 0(n 2 ) is introduced that produces schedules with minimum mean-flow time.